Biochemically Induced Variations During Some Phenological Stages in Thompson Seedless Grapevines Grafted on Different Rootstocks - Jogaiah, S.; Oulkar, D.P.; Banerjee, K.; Sharma, J.; Patil, A.G.; Maske, S.R.; Somkuwar, R.G. (South African Journal of Enology and Viticulture, 2016)
Phenological variation in Thompson Seedless grapevines grafted on different rootstocks and own rooted vines was assessed for two consecutive years and the reasons for such variations were studied through biochemical analysis. Uniform and early bud sprouting was recorded in the vines grafted on 110R rootstock and on own roots, which was attributed to increased peroxidase activity and protein content in the buds before bud burst. Increased fruitfulness on 110R rootstock and own rooted vines was attributed to the increased phosphorus and protein content of those vines and reduced vegetative vigour measured in terms of shoot length, cane diameter and pruned biomass. Thompson Seedless grafted on Dogridge rootstock recorded the highest nitrogen content, increased shoot length, cane diameter and increased pruned biomass attributing to reduced fruitfulness. The highest concentration of phenolic compounds and amino acids was recorded in the fruits produced on 110R rootstock, while it was least on St. George and own roots. Significant variation in the accumulation pattern of amino acids (especially proline and arginine) was observed, with the least proline/arginine ratio recorded on 110R rootstocks at the time of harvest, indicating the variation in the days taken for fruit ripening on different rootstocks.